2002
DOI: 10.1083/jcb.200203043
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor ligation induces the formation of dynamically regulated signaling assemblies

Abstract: Tcell antigen receptor (TCR) ligation initiates tyrosine kinase activation, signaling complex assembly, and immune synapse formation. Here, we studied the kinetics and mechanics of signaling complex formation in live Jurkat leukemic T cells using signaling proteins fluorescently tagged with variants of enhanced GFP (EGFP). Within seconds of contacting coverslips coated with stimulatory antibodies, T cells developed small, dynamically regulated clusters which were enriched in the TCR, phosphotyrosine, ZAP-70, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

55
772
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 578 publications
(828 citation statements)
references
References 55 publications
55
772
1
Order By: Relevance
“…Zap70 is rapidly localized in patches (15 s) whose intensity reaches a steady state at 3 min; Zap70 remains associated with these laterally immobile clusters for 30 min (59). In contrast, adaptor signaling proteins such as LAT, Grb2, Gads, and SLP-76 show similar initiation timing but disappear rapidly, within 1-3 min, from these structures (61). This phenomenon was also observed by Houtman et al (62), who demonstrated that early Zap70 phosphorylation showed maximal effect of 50% at 19 s following anti-CD3 T cell stimulation, occurred maximally at 30 s, and persisted throughout the 120-s experiment.…”
Section: Discussionmentioning
confidence: 56%
“…Zap70 is rapidly localized in patches (15 s) whose intensity reaches a steady state at 3 min; Zap70 remains associated with these laterally immobile clusters for 30 min (59). In contrast, adaptor signaling proteins such as LAT, Grb2, Gads, and SLP-76 show similar initiation timing but disappear rapidly, within 1-3 min, from these structures (61). This phenomenon was also observed by Houtman et al (62), who demonstrated that early Zap70 phosphorylation showed maximal effect of 50% at 19 s following anti-CD3 T cell stimulation, occurred maximally at 30 s, and persisted throughout the 120-s experiment.…”
Section: Discussionmentioning
confidence: 56%
“…The puncta containing interacting STIM1-CFP and Orai1-YFP did not colocalize with clusters containing phosphotyrosine that mark the sites of TCR clustering and activation ( Figure 1E; Bunnell et al, 2002). Thus, after TCR engagement, STIM1-CFP and Orai1-YFP closely interact in structures that are distinct from the signaling complexes that form at the activated TCR.…”
Section: After Tcr Activation Orai1-yfp and Stim1-cfp Are Seen In Pumentioning
confidence: 92%
“…Because the puncta containing STIM1-CFP and Orai1-YFP showed positive FRET indicating energy transfer, we conclude that the two proteins were within 10 nm of each other (Szollosi et al, 1998). The puncta containing interacting STIM1-CFP and Orai1-YFP did not colocalize with clusters containing phosphotyrosine that mark the sites of TCR clustering and activation ( Figure 1E; Bunnell et al, 2002). Thus, after TCR engagement, STIM1-CFP and Orai1-YFP closely interact in structures that are distinct from the signaling complexes that form at the activated TCR.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Results based on light and fluorescence microscopy of proteins and lipids, including refinements of the established fluorescence recovery after photobleaching methods and new single particle tracking methods, have led some investigators to conclude that lipid rafts comprise a minor fraction of the cell surface and others to postulate that Ͼ50% of the plasma membrane consists of lipid rafts (Kenworthy et al, 2000;Edidin, 2001). Although biochemical analyses imply a rather unitary and stable composition for lipid rafts (Brown and London, 1998), evidence from biophysical and fluorescence imaging studies raises the possibility that raft fractions may be made up of a collection of separate membrane domains with a common ability to resist detergent solubilization (Edidin, 2001;Anderson and Jacobson, 2002;Bunnell et al, 2002).We have provided new evidence for microdomain organization of plasma membrane components based upon highresolution electron microscopy and immunogold labeling of native membrane sheets (Wilson et al, 2000(Wilson et al, , 2001. Our model system is a rat mast cell tumor line, the RBL-2H3 cell, that is rich in surface expression of the high-affinity IgE receptor, Fc⑀RI (Ͼ200,000 receptors/cell).…”
mentioning
confidence: 99%